Verotoxigenic E. Coli and Its Importance in Food Hygiene - Ahmadi, Sayed Arif (Journal of Natural Sciences – Kabul University, 2022)
Verotoxigenic Escherichia coli (VTEC), also known as Shigatoxin-producing Escherichia coli (STEC), is an important pathogenic strain of E. coli that can cause diarrhea or hemorrhagic colitis in humans. The primary reservoirs for STEC O157:H7 are ruminants, particularly cattle and sheep. Other animals, such as rabbits, pigs, and poultry, can also harbor this organism. Humans acquire STEC through direct contact with animal carriers, their feces, and contaminated soil or water, or by ingesting undercooked ground beef, other animal products, and contaminated vegetables and fruits. Effective preventive measures include thoroughly cooking raw meats, pasteurizing milk, treating private water supplies, and avoiding cross-contamination from raw meats or cattle feces to other foods.